Applications of Chalcogenides: S, Se, and Te - Ahluwalia, Gurinder Kaur.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book introduces readers to a wide range of applications for elements in Group 16 of the periodic table, such as, optical fibers for communication and sensing, X-ray imaging, electrochemical sensors, data storage devices, biomedical applications, photovoltaics and IR detectors, the rationale for these uses, the future scope of their applications, and expected improvements to existing technologies. Following an introductory section, the book is broadly divided into three parts-dealing with Sulfur, Selenium, and Tellurium. The sections cover the basic structure of the elements and their compounds in bulk and nanostructured forms; properties that make these useful for various applications, followed by applications and commercial products. As the global technology revolution necessitates the search for new materials and more efficient devices in the electronics and semiconductor industry, Applications of Chalcogenides: S, Se, and Te is an ideal book for a wide range of readers in industry, government and academic research facilities looking beyond silicon for materials used in the electronic and optoelectronic industry as well as biomedical applications.
Part I: Introduction -- Fundamentals of Chalcogenides in Crystalline, Amorphous and Nanocrystalline Forms -- Techniques for Structural Investigations (Theory and Experimental) -- Nanostructured Chalcogenides -- Part II: Sulfur -- Optical Fibers -- Part III: Selenium -- Imaging and Detection -- Electrochemical Sensors -- Biomedical Applications -- Selenide Glass Fibers for Bio-Chemical Infrared Sensing -- Part IV: Tellurium -- Data Storage Devices -- Photovoltaics -- Infrared Detectors.
Keywords: Optical materials; Semiconductors; Nanotechnology; Inorganic chemistry; Optical Materials; Semiconductors; Nanotechnology; Inorganic Chemistry